2019
DOI: 10.1051/radiopro/2019041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of population radiation exposure at the edge of the exclusion zone 32 years after the Chernobyl accident: methods and preliminary results

Abstract: A case study was conducted in the village of Komarin in Belarus at the edge of the Chernobyl exclusion zone, with the aim of evaluating the spatial and temporal variability in external and internal post-accidental radiation exposure. A database containing the radioactive measurements of foodstuffs made in Komarin over a 1990–2016 period makes it possible to estimate retrospectively the internal exposure. External exposure was prospectively studied through a citizen science approach involving a group of high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
(17 reference statements)
0
9
0
2
Order By: Relevance
“…In Japan, many people met expressed their fear about radioactivity, their lack of knowledge of the long-term health effects of ionizing radiation, or their desire to better understand or personally participate in the radiological characterization of their territory (by measuring individual doses, for example) in order to better understand the radiological situation. These are actions that can be promoted in preparedness stage through citizen science projects (Bertho et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, many people met expressed their fear about radioactivity, their lack of knowledge of the long-term health effects of ionizing radiation, or their desire to better understand or personally participate in the radiological characterization of their territory (by measuring individual doses, for example) in order to better understand the radiological situation. These are actions that can be promoted in preparedness stage through citizen science projects (Bertho et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, waning interest in radiation education and ideological fixation (bipolarization) at schools remain problems (Orita et al, 2015). Bertho et al (2019) conducted a radiation education project in the post-Chernobyl Komarin village of Belarus, showing high interest in the results among students. The two high schools in Fukushima, which are the targets of this study, also have radiation protection activities led by student clubs, and the necessity of fostering a radiation protection culture by these young generations is similar in Fukushima and Belarus, and is considered important for longterm measures.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing efforts to provide information from students to students is also necessary for sustainability. The feedback following the Chernobyl accident shows the importance of organizing the networking of school initiatives, allowing the students to share their experience and initiate new projects (Bertho et al, 2019). Keeping the memory and transmitting the radiological protection culture to the young generation are crucial for maintaining the long-term vigilance on radiation protection issues.…”
Section: Discussionmentioning
confidence: 99%
“…A study using OpenRadiation has, for example, been conducted as part of TERRITORIES (www.territories.eu), a European research project that takes a citizen science approach. This study assessed the radiological quality of a territory contaminated due to the accident at Chernobyl, at the scale of a village, getting pupils at the village school to take measurements themselves and analyse them with the help of scientists involved in the project (Bertho et al, 2019). Among other things, this study demonstrated that the pupils were really keen to be involved in the project, which in turn served to get the local population interested in the practical aspects of radiological protection (Lochard et al, 2019).…”
Section: An Emerging Communitymentioning
confidence: 98%